2009
DOI: 10.1002/cmdc.200900043
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Analysis, and Biological Evaluation of Thioxoquinazoline Derivatives as Phosphodiesterase 7 Inhibitors

Abstract: PDE7 inhibitors regulate pro-inflammatory and immune T-cell functions, and are a potentially novel class of drugs especially useful in the treatment of a wide variety of immune and inflammatory disorders. Starting from our lead family of thioxoquinazolines, we designed, synthesized, and characterized a novel series of thioxoquinazoline derivatives. Many of these compounds showed inhibitory potencies at sub-micromolar levels against the catalytic domain of PDE7A1 and at the micromolar level against PDE4D2. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Importantly, depletion of PDE7B levels by lentiviral delivery of PDE7 shRNA significantly ameliorates the motor impairment subsequent to dopaminergic cell loss. Previous results from our group demonstrate that chemical inhibition of PDE7 trigger neuroprotection and diminish neuroinflammation in different models of brain diseases, including PD (Castano et al, 2009;Morales-Garcia et al, 2011;Redondo et al, 2012;Susin et al, 2012). Other authors have shown a Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Importantly, depletion of PDE7B levels by lentiviral delivery of PDE7 shRNA significantly ameliorates the motor impairment subsequent to dopaminergic cell loss. Previous results from our group demonstrate that chemical inhibition of PDE7 trigger neuroprotection and diminish neuroinflammation in different models of brain diseases, including PD (Castano et al, 2009;Morales-Garcia et al, 2011;Redondo et al, 2012;Susin et al, 2012). Other authors have shown a Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Given the important role of cAMP in the brain, specific inhibitors of PDEs are being analyzed as possible therapeutic targets for the treatment of different brain diseases (Garcia-Osta et al, 2012;Menniti et al, 2006;Sharma et al, 2013). During the last years, we have shown that different inhibitors of PDE7 are potent neuroprotective and anti-inflammatory agents in several animal models of neurodegenerative disorders, including PD (Castano et al, 2009;MoralesGarcia et al, 2011;Redondo et al, 2012;Susin et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…14,15 We have also shown that our compounds are able to increase cAMP in lymphocyte cultures. 16 Regarding advanced studies in vivo, we have proved that PDE7 inhibitors belonging to the quinazoline family enhance neuroprotection and decrease neuroinflammation in well-characterized cellular and animal models of Parkinson's disease, 17 spinal cord injury, 18 stroke, 19 and also Alzheimer's disease. 20 More recently, we have reported also in vivo efficacy of the furan type PDE7 inhibitors in an animal model of multiple sclerosis.…”
mentioning
confidence: 99%
“…The data set is characterized by a high structural diversity since it is formed by iminothiadiazoles, 28,29 benzene sulfonamides, 30 quinazolines, 16 thiazoles, 31 and spirotricyclic derivatives, 32 among others (Figure 1). …”
mentioning
confidence: 99%
“…26) Not only quinoline but also some quinazoline based derivatives were reported to have potent PDE4B inhibition such as compounds (8)(9)(10)(11) and (12)(13)(14) that have been recently identified to be selective PDE4B inhibitors in the in vitro assay. 27,28) In addition, nitraquazone having good inhibitory activity with IC 50 =1.9 µM (15) was identified as promising (PDE4) inhibitor. 29) Moreover 4-substituted-6-nitro quinazoline derivatives compound (16) had been reported to inhibit TNF-α production with unique anti-inflammatory effect.…”
Section: )mentioning
confidence: 99%